2021
DOI: 10.3390/ijerph182412999
|View full text |Cite
|
Sign up to set email alerts
|

Precarious Job Makes Me Withdraw? The Role of Job Insecurity and Negative Affect

Abstract: An expanding “gig” economy has changed the nature of employment; thus, researchers have recently focused on exploring the role of job precariousness in the workplace. However, little research attention has been given to understanding why, how and when job precariousness leads to employees’ negative behavioral outcomes in the service-oriented industry. In the current study, we examined job insecurity as a mediator and employees’ negative affect as a moderator in the relationship between job precariousness and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Thus, future studies can predict work deviant behavior by considering additional personal (e.g., commitment, locus of control, value orientation, Machiavellianism) and situational (e.g., boredom, job characteristic) factors to enrich our findings. On the other hand, although past research recognizes the positive direct effect of job precariousness and job insecurity on withdrawal behavior ( Zheng et al, 2021 ), counterintuitively, Vo-Thanh et al (2021) demonstrated that perceived health risk associated with COVID-19 has a positive influence on employee job performance. As explained by Vo-Thanh et al (2021) , the economic menace caused by COVID-19 is extremely acute on a worldwide scale for every sector, especially in the hospitality and tourism industry.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, future studies can predict work deviant behavior by considering additional personal (e.g., commitment, locus of control, value orientation, Machiavellianism) and situational (e.g., boredom, job characteristic) factors to enrich our findings. On the other hand, although past research recognizes the positive direct effect of job precariousness and job insecurity on withdrawal behavior ( Zheng et al, 2021 ), counterintuitively, Vo-Thanh et al (2021) demonstrated that perceived health risk associated with COVID-19 has a positive influence on employee job performance. As explained by Vo-Thanh et al (2021) , the economic menace caused by COVID-19 is extremely acute on a worldwide scale for every sector, especially in the hospitality and tourism industry.…”
Section: Discussionmentioning
confidence: 97%
“…Positive deviance has been found to be an indicator of employees' intrapreneurial behavior ( Kibirango, Munene, Balunywa, & Obbo, 2017 ) and engagement ( Sharma, 2021 ). Globally, the current literature acknowledges that precarious work conditions are potential drivers of work deviance ( Zheng, Ding, Chen, Wu, & Cai, 2021 ). In the hotel context, recent research shows that perceived health risks associated with COVID-19 can positively influence employees' perceived job insecurity, which affects job performance negatively ( Vo-Thanh et al, 2021 ) and emotional exhaustion positively ( Vo-Thanh, Vu, et al, 2022 ).…”
Section: Context Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…The lack of information will cause all kinds of rumors and suspicions and enhance the distrust of the organization, so that the organizational crisis cognition is assessed as "threat" (Roskies and Christiane, 1990). When the organization is in turmoil and has operational difficulties, employees, under the negative perception of organizational crisis, will think that organization will cause difficulties to their own work and lives, leading to pessimistic views about the sustainability and worth of their work (Zheng et al, 2021). This situation escalates feelings of confusion, panic, anxiety and job insecurity.…”
Section: Cognitive Appraisal Theory Of Stressmentioning
confidence: 99%
“…For example, excessive workload, increased job demands on free time, tight deadlines, exposure to emotional distress at work, and job burnout threats. Workers' perceptions of these precarious circumstances reflect psychological contracts and insecurity, which erode work quality and lead to withdrawal behaviors (Zheng et al, 2021 ). Given that, in this study, I develop an index of emotional precariousness that encompasses various workers' subjective experiences of vulnerability and powerlessness at work to expand the psychological dimension of precarity during COVID-19, in addition to employment instability and job insecurity, two conventional measures of employment precarity in current scholarship.…”
Section: Conceptualization Of Employment Precarity In Europementioning
confidence: 99%